3D microcarrier system for efficient differentiation of human induced pluripotent stem cells into hematopoietic cells without feeders and serum. (July 2013) - Lu, Shi-Jiang; Kelley, Tim; Feng, Qiang; Chen, Allen; Reuveny, Shaul; Lanza, Robert; Oh, Steve KW
Background: Human embryonic stem cells (hESCs) have been derived and maintained on mouse embryonic fibroblast feeders to keep their undifferentiated status. To realize their clinical potential, a feeder-free and scalable system for large scale production of hESCs and their differentiated derivatives is required.Materials & methods: hESCs were cultured and passaged on serum/feeder-free 3D microcarriers for five passages. For embryoid body (EB) formation and hemangioblast differentiation, the medium for 3D microcarriers was directly switched to EB medium.Results: hESCs on 3D microcarriers maintained pluripotency and formed EBs, which were ten-times more efficient than hESCs cultured under 2D feeder-free conditions (0.11 ± 0.03 EB cells/hESC input 2D vs 1.19 ± 0.32 EB cells/hESC input 3D). After replating, EB cells from 3D culture readily developed into hemangioblasts with the potential to differentiate into hematopoietic and endothelial cells. Furthermore, this 3D system can also be adapted to human induced pluripotent stem cells, which generate functional hemangioblasts with high efficiency.Conclusion: This 3D serum- and stromal-free microcarrier system is important for future clinical applications, with the potential of developing to a GMP-compatible scalable system.